Velocity 2016, New York, New York : video compilation. (O'Reilly Media, 2016)
"How did Twitter turn hundreds of services, tens of thousands of machines, and millions of requests per second into a unified, performant application? How does Instagram test and deploy code to a fleet of thousands of web servers in as little as 10 minutes forty times per day? How did GameStop migrate 12 ecommerce websites with millions of users from dedicated hardware to the cloud in three months? These are just a few of the stories told by 97 industry experts at the four intense days devoted to web operations, performance, and DevOps known as Velocity New York 2016. Want to see how Uber, Etsy, Netflix, HPE, Pivotal, Tumblr, SOASTA, Catchpoint, and more do it? Get this video compilation and you'll enjoy watch-when-you-want access to each of the conference's 10 tutorials (3.5 hours each), 50 sessions (40 minutes each), and 18 keynotes."--Resource description page